ISSUES OF STAFFING OF THE DIPLOMATIC SERVICE OF THE REPUBLIC OF UZBEKISTAN - Tursunova Malikahon Ulugbekovna (Scholar Express Journals, 2022)
The article addresses the issues of staffing of the diplomatic service in the Republic of Uzbekistan. Based on the ongoing reforms on foreign policy of Uzbekistan, it analyzes the personnel affairs of the diplomatic service, examines the requirements for diplomatic staff, its professional qualities, due selection and training, the procedures of hiring diplomatic workers in Uzbekistan, organizing competitions and legal basis thereof. Proposals and recommendations are formulated that are of practical importance for the further improvement of national legislation in the field of staffing the diplomatic service of the Republic of Uzbekistan
Keywords: Diplomacy; professional qualities of a diplomat; national legislation; diplomatic law